Experimental study on a laboratory-scale archimedes screw turbine using pitch-to-diameter ratio for low-head hydropower - Helmizar Helmizar; Nurcholish Windiharto; Yovan Witanto; Afdhal Kurniawan Mainil; Rahmat Iman Mainil; Khotso Sai (Politeknik Negeri Lhokseumawe, 2025)
The Archimedes screw is a hydropower technology well-suited for low-head applications This study investigates the performance of a laboratory-scale Archimedes screw turbine for low-head hydropower applications by varying pitch-to-diameter ratio (P/D = 0.3, 0.38, 0.45, 0.52) and inclination angle (β = 22°, 25°, 27°). Experiments were conducted in a controlled water flow environment to evaluate torque, power output, and efficiency at different rotational speeds. Results indicate that both P/D and β significantly influence energy conversion. The highest performance was achieved at P/D = 0.45 and β = 22°, producing a peak torque of 0.36 Nm, a power output of 2.4 W, and a maximum efficiency of 52.37%. Lower inclination angles contributed to improved hydraulic energy capture due to better water filling and reduced slippage. These findings highlight the importance of optimizing geometric parameters to enhance turbine performance in small-scale, sustainable energy systems. The results offer design guidance for implementing Archimedes screw turbines in rural or off-grid low-head hydropower scenarios.